The Roles and Duties in Dispute Mediation of Village Headmen and Subdistrict Heads: A Case Study in Mae Lao District, Chiang Rai Province - Poowiangjun, Pukkapong; Imiwat, Prayoon; Inthep, Arunee (Journal of Public Administration Chiang Rai Rajabhat University, 2024)
The research aims to objectives of the Study the roles and duties in dispute mediation of village headmen and subdistrict heads. To compare the roles and duties in dispute mediation of village headmen and subdistrict heads with different backgrounds. This research utilizes quantitative research methods, with a sample population of 63 participants. Data were analyzed using percentage, mean, standard deviation, t-test, and F-test. The study results revealed that the overall roles and duties in dispute mediation of village headmen and subdistrict heads in Mae Lao District, Chiang Rai Province, were found to be at a high level. The comparative analysis of the roles and duties in dispute mediation of village headmen and subdistrict heads in Mae Lao District, Chiang Rai Province, with different backgrounds, revealed that village headmen and subdistrict heads who had undergone training versus those who had not, under the Village Headman Training Program from the College of Local Administration, as well as those with different education levels and lengths of service, performed their duties in dispute mediation roles with no statistically significant difference.